Respuesta :
Respuesta:
x = 3, -12
Explicación paso a paso:
x^2 + 9x - 36 = 0
datos
a = 1
b = 9
c = - 36
x = -b ±[tex]\sqrt{b^{2} - 4ac } / 2a\\[/tex]
x= -9 ±[tex]\sqrt{9^{2} -4(1)(-36)} / 2(1)[/tex]
x = -9 ± [tex]\sqrt{9^{2}+144 }[/tex] / 2
x = -9 ± [tex]\sqrt{81 + 144 } / 2[/tex]
x = -9 ± [tex]\sqrt{225} /2[/tex]
x = -9 ± 15 / 2
[tex]x_{1}[/tex] = [tex]\frac{-9 + 15}{2}[/tex] [tex]x_{2}[/tex] = [tex]\frac{-9-15}{2}[/tex]
[tex]x_{1}[/tex] = [tex]\frac{6}{2}[/tex] [tex]x_{2}[/tex] = [tex]\frac{-24}{2}[/tex]
[tex]x_{1}[/tex] = 3 [tex]x_{2}[/tex] = -12